Optimization of Centrifugal Pump Impeller to Increase Pump Hydraulic Efficiency Using Solidworks Flow Simulation - Victor, Eldred Emil; Ashari Kasmin (Progress in Engineering Application and Technology, 2022)
The performance of a centrifugal pump is determined by the impeller geometry. Modifying geometric parameters such as outlet blade angle has a substantial influence on discharge head and efficiency because the blade pressure blade rises when angle. Since the pump operated continuously it is prone to wear and tear due to its function and therefore is vulnerable to failures that affect the pump performance. This research was conducted to enhance pump performance by optimizing impeller outlet blade angle. This research methodology consists of a few stages. Initially, the original pump is measured. Then, the measured parameter will be used to design the pump using Solidworks software. For impeller optimization, the outlet blade angle will be optimized by varying its outlet blade angle (β2) from β2=29˚, 30˚, 31˚, 32˚, 33˚, 34˚ and 35˚. Then the best outlet blade angle for the first optimization will be further refined which varying from β2=32.8˚, 32.9˚, 33˚, 33.1˚, 33.2˚ and 33.3˚ by using Solidworks Flow Simulation Software. The optimum β2 will be used for the new optimized impeller. As for results, the original impeller shows a 15.72m discharge head and 51.48% efficiency. Then the optimized outlet blade angle that produces optimum performance was outlet blade angle β2=33˚, with a 15.87m discharge head and 56.27% efficiency. Furthermore, the outlet blade angle β2=33˚ was further refined and shows that the outlet blade angle that produce the best performance was β2=33.1˚, which yield 15.9m discharge head and 56.53% efficiency. In conclusion, increasing the outlet blade angle shows a significant improvement in discharge head and efficiency as in theory by previous researchers. Then, it shows that using Solidworks Flow Simulation helps to achieve these research objectives.